The Autonomous Learning Level of Speaking Skill in English Education Study Program - Ade Andriani, Fitri; Sujarwati, Iis (J-SHMIC : Journal of English for Academic, 2025)
This study aimed to assess the level of independent learning regarding speaking skills within the English Language Education Study Program. A quantitative descriptive design was utilized to analyze the speaking skill levels of students. A questionnaire consisting of 30 questions served as the instrument for this study. The researcher used likert scale in this research. The subjects included first-semester students from the English Language Education Study Program at the University of Bengkulu. The total population was comprised of 110 students, with 75 selected as research samples using a volunteer sampling technique, and participants volunteered for the study. The results revealed that the highest score was recorded for the statement, "I like to learn English speaking," which scored 3.59, indicating strong student interest in speaking English. Conversely, the lowest score was for the statement, "I speak English with friends," which scored 2.37, suggesting a lack of practice and confidence in using English in informal settings. These findings indicated that while students demonstrated an interest in developing their speaking skills and tried to improve, they encountered challenges in applying their knowledge in real-life situations. Overall, the learning level of independent speaking skills among first-semester English Language Education Program students was generally rated as moderate to high. These results underscore the need for targeted approaches to boost students' confidence and competence in speaking English outside the classroom.